(untitled) (The Journal of Psychology and Sociology, 2016)
This article discusses the social and economic aspects of modern family life and problems of family upbringing. In modern conditions there are processes of modi-fication as the family as a whole, and the individual elements of marital relations. Transformation processes of marriage and family, expressed in the separation of the institutions of parenthood, a matrimony and kinship, led to the emergence of differ-ent family models, among which we can highlight single parenting. It is proved that the main causes of changes in family relationships, including the reduction of the role of men in the process of primary socialization, it is necessary to look directly into the sphere of family relations (including their psychological, econom-ic, legal aspects), as well as in the area of social economic trends in the development of modern society in general. The reason (or reasons) of the fact that basic physical and psychological stress associated with raising children in a modern family falls on women – the result of a gradual change of role the economic functions of the family members, a change of status roles of men and women and, finally, the change of the family. Regard-less of the nature of the family, motherhood and fatherhood are two different parenting institutes; also have their own specific functions, depending on the socio-cultural fac-tors. In the context of the study single-parent families should be noted that parenthood institutions: maternity and paternity while preserving the traditional features can be real-ized in the context of different economic strategies and models of family upbringing. The article notes that the analysis of the problems of parenting in the modern Kazakh society more important is the study of correlations between the distributions of socio-economic and gender roles in the family and the effectiveness and quality of family upbringing.